Characteristics of Cooperative Debtor Households in Maluku Province - Jean Claire Nicolette Matatula; Sri Muljaningsih; Marlina Ekawaty (Journal of International Conference Proceedings, 2022)
Cooperatives are one of the recognized microfinance institutions in Indonesia, with the aim of improving the welfare of members in particular and society in general. This is in line with the goals of the SDGs to end poverty, ensure a healthy life and prosperity for all. Cooperatives are considered easier to reach the lower middle class, especially in accessing loans and having problems with collateral. This paper examines the characteristics of cooperative debtor households in Maluku Province. This research uses descriptive analysis based on the SUSENAS 2021 data by Central Bureau Statistic. As a result, most of those who access loans in cooperatives are married men aged 30 years and over with education below high school and informal employment status, live in rural areas outside the provincial capital, have a total of 4 household members and are not poor households, however have health complaints. Based on these results, it can be concluded that future government policy is to encourage cooperatives to innovate so that it is easier to reach poor households in order to minimize the occurrence of loans in the informal sector (family, friends or online loans) which have the potential to increase conflict and prolonged poor status.Â Keywords: Characteristics, Household, Cooperative Loan, Maluku, Descriptive Analysis, SUSENAS.